Gambaran Faktor Risiko Preeklampsi dan Eklampsi pada Ibu Hamil di Rumah Sakit Bhayangkara Makassar - Ririn Ramadhani Ridwan; Suzanna S. Pakasi; Andi adil; M. Hamsah; Haizah Nurdin (Universitas Muslim Indonesia, 2023)
The high maternal mortality rate requires knowledge about the risk factors for preeclampsia and eclampsia which can cause maternal death. This study aims to describe the risk factors for preeclampsia and eclampsia in pregnant women at Bhayangkara Hospital Makassar in 2019-2021. This research is a retrospective descriptive study conducted at Bhayangkara Hospital Makassar in 2019-2021. From the results of the study it was found that the number of patients with a diagnosis of preeclampsia who came to the Obstetrics and Gynecology Outpatient Installation at Bhayangkara Hospital Makassar was 15 medical records, the number of patients with a diagnosis of preeclampsia who were treated at the inpatient installation found 75 medical records, the number of patients with a diagnosis of There were 10 medical records for eclampsia treated in inpatient installations. Pregnant women with the highest risk of preeclampsia on outpatient or inpatient care were aged 20-35 years, multiparas, no history of hypertension, incomplete ANC, pregnancy interval <2 years, last high school education, and housewives. Pregnant women with the highest risk of eclampsia at hospitalization were aged 20-35 years, primipara, no history of hypertension, incomplete ANC, pregnancy interval <2 years, last high school education, and housewives. The most dominant risk factor is age, namely at the age of 20-35 years.